Análisis sobre el efecto de la norma NIIF, sección 34 actividades especiales, en el estado de situación financiera de apertura en la empresa “Eco Comercial s.a” (2018)
The implementation of the International Financial Reporting Standards represents an important effort for SMEs for their planning and implementation, which in turn allows them to comply with the provisions of Law 1314 of 2009. However, the biggest question that entrepreneurs ask themselves what is the impact on your financial information and the costs of such implementation.